Tinjauan Asas Kebebasan Berkontrak Dalam Perjanjian Lisensi Perangkat Lunak Blackberry - Amora P, Monica Ava; , Inayah, S.H., M.H; , Aristya Windiana Pamuncak, S.H., LL.,M (2016)
This study aims to describe: (1) application of the principle of freedom of contract in the BlackBerry software license agreement and (2) the legal protection of the parties involved with the software license agreement BlackBerry, from the aspect of the principle of freedom of contract. This type of research is qualitative descriptive. The approach method in this research is normative juridical approach. Respondents in the study is the Head or Deputy PT Indosat Branch of Surakarta. Conclusion: (1) The application of the principle of freedom of contract BlackBerry Software License Agreement. Elements are met: (a) the freedom to make or not make an agreement and (b) the freedom to choose who will make the appointment. Elements that are not being met, namely (a) the freedom to determine the form of an agreement, (b) freedom to receive or deviate the statutory provision which is optional (specify the content of the agreement), (c) the freedom to define how to make an appointment. (2) Legal protection for the parties involved with the BlackBerry Software License Agreement, Elements is fulfilled only two, then the consumer protection BlackBerry users do not obtain legal protection. The reason, Indonesia as one of the members of the international community can not be separated from international trade which has a container called the World Trade Organization (WTO).